Privacy Regulation and Quality-Enhancing Innovation - Yassine Lefouili; Leonardo Madio; Ying Lei Toh (Center for Economic Studies and ifo Institute (CESifo), 2023)
We analyze how a privacy regulation taking the form of a cap on information disclosure affects quality-enhancing innovation incentives by a monopolist—who derives revenues solely from disclosing user data to third parties—and consumer surplus. If the share of privacy-concerned users is sufficiently small, privacy regulation has a negative effect on innovation and may harm users. However, if the share of privacy-concerned users is sufficiently large, privacy regulation has a positive effect on innovation. In this case, there is no trade-off between privacy and innovation and users always benefit from privacy regulation.
Keywords: D83; L15; L51; 330; privacy regulation; data disclosure; innovation